Community-Based Strategies for Sustainable Peatland Ecosystem Protection - Rajagukguk, Jenni Ria (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Tropical peatland ecosystems play a crucial role in global climate regulation by storing large amounts of carbon, yet they continue to experience severe degradation due to drainage, land conversion, and recurring fires. Conventional peatland restoration approaches that rely solely on technical interventions often fail to achieve long-term sustainability because they insufficiently address social and institutional dimensions. This study aims to examine and formulate community-based strategies for sustainable peatland ecosystem protection by integrating hydrological restoration, fire prevention, and socio-economic empowerment. The research adopts a qualitative approach using a literature study design, drawing on peer-reviewed journal articles, institutional reports, and relevant policy documents related to peatland management and community participation. Data were analyzed through thematic content analysis to identify key patterns, practices, and strategic elements that support effective community engagement. The findings indicate that community-based fire management, participatory hydrological restoration, and the development of peat-compatible livelihoods significantly enhance the effectiveness and sustainability of peatland protection efforts. Strong local institutions, incentive alignment, and policy support further strengthen long-term adoption. The study concludes that positioning local communities as co-managers rather than passive beneficiaries is essential for achieving resilient and sustainable peatland ecosystem protection.